LOGAM MULIA EMAS : ALAT INVESTASI UTAMA BAGI GENERASI SANDWICH ? - Hardiyanti, Widhian; Wulandari, Sartika; Santoso, Ignatius Hari (Jurnal Ekonomi Manajemen, 2021)
This study aims to analyze the differences in attitudes between sandwich generations investing in precious metals in carrying out parenting patterns for parents and children. This research used 67 respondents who specifically consisted of 27 respondents who owned gold as the main investment tool, while the rest were groups of respondents who had investment tools other than gold precious metals through mutual funds.By using the Mann Whitney method, it can be concluded that there are different attitudes in the Sandwich generation who invest in gold and those who invest in other than precious metals in carrying out parenting patterns for parents and children. Furthermore, gold precious metal is not an appropriate investment tool for the sandwich generation because it requires a larger fundraiser and a high level of discipline